ТYPES OF DIRECT SPEECH IN DOBRICA ĆOSIĆ'S NOVEL THE ROOTS (Heritage, 2022)
The paper discusses the specific methods of forming the direct speech in Dobrica Ćosić's novel The Roots. In order to describe the speech diversity of the novel and to make the systematic survey of all the syntactic constructions with direct speech, the linguo-stylistic methods are employed. Although The Roots are primarily associated with internal monologue as a dominant form of narrative, the paper will show that the direct discourse plays an important role in Dobrica Ćosić's novel, with its own individual characteristics, due to the fact that the phenomenon of communication is based on dialogue, while the true nature of reported and reporting discourse is dialogical as well.
Keywords: author speech, dialogue, internal monologue, direct speech